Study of Chicken Meat Business Management Strategy in Efforts to Increase Competitiveness (Case Study on Mrs. Hasnia's Chicken Meatball Business in Rahandouna Village Poasia District Kendari) - Aprianto, Denny; Rianda, La; Abdullah, Sukmawati (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
The chicken meatball processing business located in Rahandouna Village, Poasia District, Kendari City, is a home-based company that produces chicken meatballs. This research aims to determine the strengths, weaknesses, opportunities, and threats and determine a competitive strategy using the SWOT analysis method. SWOT analysis can provide accurate research results to formulate competitive strategies that maximize strengths and opportunities. But at the same time, it minimizes weaknesses (weaknesses) and threats (threats). The research results show a strength score of 1.95, weaknesses of 0.80, opportunities of 1.65, and threats of 0.98. So, it was found that Mrs. Hasnia's business position was in a very favorable situation; the company had opportunities and strengths to take advantage of existing opportunities. The strategy that must be implemented in this condition is to support aggressive growth policies (growth-oriented strategy).